Linear ODE with nonlocal boundary conditions and Green’s functions for such problems - Roman, Svetlana; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2010)
In this article we investigate a formula for the Green’s function for the n-order linear differential equation with n additional conditions. We use this formula for calculating the Green’s function for problems with nonlocal boundary conditions.